Innovative methods and technologies for electronic discourse analysis - Lim, Hwee Ling, 1964-; Sudweeks, Fay. (Hershey, PA : Information Science Reference, 2014)
'This book highlights research, applications, frameworks, and theories of online communication to explore recent advances in the manipulation and shaping of meaning in electronic discourse'--Provided by publisher.
Includes bibliographical references (p. 459-508) and index.
Keywords: Online chat groups; Discourse analysis; Communication -- Technological innovations